Capacity Expansion of Power Generation Systems with Uncertainty in the Prices of Primary Energy Resources - Levin, Nissan; Tishler, Asher; Zahavi, Jacob (Management Science, 1985)
In capacity expansion studies of power generation systems, the uncertainty in the prices of the primary energy resources is a major concern. The approach presented in this paper accounts for this uncertainty by mapping the probability distribution of the installed capacity for any given distribution of the fuel prices. Given the probability density function and the cumulative distribution of the installed capacity, a variety of performance measures is derived, including the expected value, the mode, and the variance of the installed capacity, and the expected total costs. Results are obtained analytically for a 2-unit system using a breakeven point analysis approach to find the optimal mix for any given set of fuel prices under the assumption of normally distributed primary energy prices.